Value engineering for value creation in the automotive industry / Aliza Ramli, Suzana Sulaiman and Falconer Mitchell - Ramli, Aliza; Sulaiman, Suzana; Falconer, Mitchell (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper intends to explore the adoption of Value Engineering (VE) as a value creation tool within Malaysian automotive organizations. VE relates to a systematic and multi-disciplinary team approach adopted by organizations which analyze the functional requirements of new and existing products, projects or services. The aim is to achieve the essential function at the lowest overall cost while maintaining customers’ optimum value assurance. Dual research methods comprising of case study and survey were adopted in this study. The survey findings were able to confirm and extend the case study findings. The findings indicate that VE is a common and routine activity within the automotive industry. Further, the stage model adopted in this study provides the understanding of VE innovation by confirming that the identified stages do exist and by indicating the contingencies, it determines whether the stages of adoption happen in a predictable order.